Chimpanzee (Pan troglodytes schweinfurthii) grouping patterns in an open and dry savanna landscape, Issa Valley, western Tanzania. Issue 163 (February 2022) - Giuliano, Camille; Stewart, Fiona A.; Piel, Alex K.
Abstract: Fission-fusion societies are social systems in which individuals belonging to the same community are rarely all together but rather spend most of their time in temporary parties. This flexible social organization is assumed to be an adaptation that balances advantages and costs of group living in a fluid way as resources and constraints shift through space and time. It has been argued that this flexibility freed hominins from the foraging constraints caused by living in large groups. Given their close genetic relationship to humans and because they represent the classic case of a fission-fusion society, chimpanzees have often been used as referential models to understand human social evolution. Determinants of chimpanzee party size have been widely studied for decades across several communities. However, we lack data from open and dry sites—which closely resemble those reconstructed for Plio-Pleistocene hominins—on communities that potentially face similar environmental constraints as early hominins did. We investigated chimpanzee ( Pan troglodytes schweinfurthii ) grouping patterns on a recently habituated community living in the savanna-woodland mosaic landscape of the Issa Valley, western Tanzania, by following chimpanzees daily and recording party size every hour. Our results revealed that party size at Issa 1) followed seasonal fluctuations in food availability, 2) increased in the presence of swollen females, and 3) was higher in open vegetation, which potentially presents a high predation risk. Furthermore, we found the Issa community to be highly cohesive compared with the majority of other communities, possibly due to a combination of its small size and potential threats characterizing its home range. Our study fills a gap in our knowledge of chimpanzee sociality by exploring grouping pattern determinants in an East African understudied biome and highlights what elements of early hominin social behavior may have evolved in Late Pliocene landscapes.